Single Dose of Oral Azithromycin With or Without Amoxicillin to Prevent Peripartum Infection in Laboring, High-Risk Women in Cameroon: A Randomized Controlled Trial. Issue 5 (November 2021) - Subramaniam, Akila; Ye, Yuanfan; Mbah, Rahel; Mbunwe, Doreen M.; Pekwarake, Seraphine; Bunwi, Edwan Yui; Fondzeyuf, Anthony; Ngong, Mary G.; Dionne-Odom, Jodie; Harper, Lorie M.; Jauk, Victoria C.; Carlo, Waldemar A.; et al.
Abstract : OBJECTIVE: To compare the effectiveness of single-dose azithromycin, with or without amoxicillin, with placebo to prevent peripartum infection in laboring women. METHODS: We conducted a multicenter, three-group, double-blind randomized controlled trial of women with viable term nonanomalous pregnancies with either prolonged labor of 18 hours or longer or rupture of membranes for 8 hours or longer in Cameroon. Women with chorioamnionitis before randomization, study drug contraindications, or planned cesarean births were excluded. Women were randomized to oral azithromycin 1 g–placebo (group 1), oral azithromycin 1 g–oral amoxicillin 2 g (group 2), or placebo–placebo (group 3). All groups received usual care, including antibiotics given at the health care professional's discretion. The primary outcome was a composite of maternal peripartum infection or death from any cause up to 6 weeks postpartum. Two primary comparisons (group 1 vs group 3 and group 2 vs group 3) were planned. We estimated that 241 women per group (planning for 750 total) would provide 80% power at two-sided α=0.05 (0.025 per comparison) to detect a 50% effect size assuming 20% baseline composite infection rate. RESULTS: From January 6, 2018, to May 15, 2020, 6, 531 women were screened, and 756 (253 in group 1, 253 in group 2, and 250 in group 3) were randomized. Baseline characteristics (including body mass index, duration of rupture of membranes or labor, and parity) were balanced across groups, except for maternal age. More than 60% of women in each group received usual-care antibiotics: more than 90% penicillin and approximately 50% for prolonged rupture of membranes across all study groups. Composite outcome incidences were similar in antibiotic groups 1 (6%) and 2 (7%) compared with placebo group 3 (10%) (RR 0.6, 95% CI 0.3–1.2; 0.7, 95% CI 0.4–1.3, respectively). Chorioamnionitis and wound infection were significantly lower in group 2 (3.2% vs 0.4% and 4% vs 0.8% respectively, both P =.02) compared with group 3. There were no differences in other maternal or neonatal outcomes including neonatal infection. CONCLUSION: A single dose of oral azithromycin with or without amoxicillin for prolonged labor or rupture of membranes at term did not reduce maternal peripartum or neonatal infection. Observed lower than expected infection rates and frequent usual-care antibiotic use may have contributed to these findings. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT03248297. FUNDING SOURCE: Merck for Mothers Investigator Studies Program grant. Abstract : Single oral-dose azithromycin, with or without amoxicillin, for prolonged labor or rupture of membranes at term did not reduce maternal peripartum or neonatal infection or death in a setting with frequent antibiotic use as part of usual care.